Incubation of ovine scrapie with environmental matrix results in biological and biochemical changes of PrPSc over time - Maddison, Ben C.; Spiropoulos, John; Vickery, Christopher M.; Lockey, Ricahrd; Owen, Jonathan P.; Bishop, Keith; Baker, Claire A.; Gough, Kevin C. (BioMed Central, 2015)
Ovine scrapie can be transmitted via environmental reservoirs. A pool of ovine scrapie isolates were incubated on soil for one day or thirteen months and eluted prion was used to challenge tg338 mice transgenic for ovine PrP. After one-day incubation on soil, two PrPSc phenotypes were present: G338 or Apl338ii. Thirteen months later some divergent PrPSc phenotypes were seen: a mixture of Apl338ii with either G338 or P338, and a completely novel PrPSc deposition, designated Cag338. The data show that prolonged ageing of scrapie prions within an environmental matrix may result in changes in the dominant PrPSc biological/biochemical properties.